RAPAT TAHUNAN SIDANG SEBAGAI MEKANISME PERENCANAAN (Tinjauan Fungsi Manajemen Perencanaan A’la KGPM) - Benyamin, Mario Marchellino (PT. Giat Konseling Nusantara, 2026)
Congregational growth in a church is the desire of every congregational leader. A church must be strong in its ministry, but also in its organizational capacity. Therefore, a church must have a strong management foundation and sufficient knowledge to ensure its effective management. Planning, as a fundamental management function, influences the implementation of programs designed to support its ministry. The Minahasa Protestant Church (Kerjap) is a local church in North Sulawesi with a distinctive characteristic: its adherence to a congregational church governance system. This system of governance allows each congregation (as the congregation is called) the freedom to contribute directly to planning, both long-term and short-term. The KGPM's unique approach to planning precedes evaluation, ensuring the church's planning program is continually updated annually.